Exogenous Melatonin Alleviates Oxidative Damages and Protects Photosystem II in Maize Seedlings Under Drought Stress - Huang, Bo; Chen, Yang-Er; Zhao, Yu-Qing; Ding, Chun-Bang; Liao, Jin-Qiu; Hu, Chao; Zhou, Li-Jun; Zhang, Zhong-Wei; Yuan, Shu; Yuan, Ming (Frontiers in Plant Science, 2019)
The protective role of melatonin in plants against various abiotic stresses have been widely demonstrated, but poorly explored in organ-specific responses and the transmission of melatonin signals across organs. In this study, the effects of melatonin with the root-irrigation method and the leaf-spraying method on the antioxidant system and photosynthetic machinery in maize seedlings under drought stress were investigated. The results showed that drought stress led to the rise in reaction oxygen species (ROS), severe cell death, and degradation of D1 protein, which were mitigated by the melatonin application. The application of melatonin improved the photosynthetic activities and alleviated the oxidative damages of maize seedlings under the drought stress. Compared with the leaf-spraying method, the root-irrigation method was more effective on enhancing drought tolerance. Moreover, maize seedlings made organ-specific physiological responses to the drought stress, and the physiological effects of melatonin varied with the dosage, application methods and plant organs. The signals of exogenous melatonin received by roots could affect the stress responses of leaves, and the melatonin signals perceived by leaves also led to changes in physiological metabolisms in roots under the stress. Consequently, the whole seedlings coordinated the different parts and made a systemic acclimation against the drought stress. Melatonin as a protective agent against abiotic stresses has a potential application prospect in the agricultural industry.